Smart Box / Muhammad Aiman Mohd Zaki ... [et al.] - Mohd Zaki, Muhammad Aiman; Halidan, Saiful Hadi; Zaidi, Muhammad Hafiz; Mohd Rosdi, Muhammad Ariff Iskandar; Mohd Zohan, Mohamad Nazim (2022)
Our company produces the ‘Smart Box,' which is the most recent creative invention in a delivery item that is very easy to use for all levels of users. We all know that nobody wants their packages to break down or crash. As a result, we came up with the concept of modifying and upgrading the mailbox to a Smart Box, which is integrated with cutting-edge technology. As we all know, things that will be shipped will be packaged in the form of parcels, but we frequently hear complaints and comments from netizens since many items sent are damaged or lost when they arrive at their destination, especially when the customer is not at home, this Smart Box is significant since it can prevent the item from being damaged or broken as a result of actions of irresponsible people, animals, or the effects of bad weather. Customers who use Smart Box are certain that they will have no doubts or concerns about the condition of the items. We evaluated the characteristics of our target market. The 'Smart Box,' which is ideal for all levels of users, is available for order through our service. Our core target market for ‘Smart Box' is those who love online shopping as well as people who are busy working and often not at home, such as students, office hour employees, and the elderly. As a result, people will have higher confidence in our products and will be able to simplify the process of having items delivered to their homes by couriers. As a solution, we created a line of different and unique Smart Boxes to suit the expectations of customers who want their belongings to be protected while also increasing the postal service company's reputation. There are various limitations to the existing mailbox product on the market today that customer should be aware of and be cautious about, such as the inability to use effectively and the inflexibility of time. As an outcome, the 'Smart Box' is a new idea for secure mailboxes that can be accessed by users of all levels. Our existing 'Smart Box,' as approved by SIRIM and the Ministry of Science, Technology and Innovation (MOSTI), produces good and safe product use. This is due to our company's strong commitment to all of our consumers who purchase and utilize our products. The ultimate goal of our business is to become a leading and competitive manufacturer of new products for both the domestic and worldwide markets.